GROWTH AND CROPPING OF SEVERAL SCAB- -RESISTANT APPLE CULTIVARS ON SIX ROOTSTOCKS - Ireneusz Sosna (Acta Scientiarum Polonorum: Hortorum Cultus, 2005)
The experiment was conducted at Fruit Experimental Station Samotwór near Wroclaw in the years 1998–2003, The aim of the experiment was to estimate the influence of six rootstocks on the growth, cropping and fruit quality of some new scabresistant apple cultivars. Two of the cultivars were Polish –Waleria and Sawa, and four of them were Czech – ‘Rosana’, ‘Rubinola’, ‘Rajka’ and ‘Topaz’. In the spring of 1998 maiden trees on rootstocks M.9, P2, P60, P16, P22 and M.27 were planted at the spacing 3.5×1.2 m (2380 trees/ha). The results of six-year-long studies confirmed that ‘Rubinola’ and ‘Rajka’ were characterised by the strongest vigour (the lowest crop efficiency indices – CEI), while ‘Rosana’ grew very weakly (the highest CEI). Fruit quality in terms of presentation and taste was the best in the case of ‘Rubinola’. ‘Sawa’, ‘Rubinola’ and ‘Topaz’ had the biggest potential for commercial production. The rootstocks M.9 and P60 proved to be the most useful for the studied apple cultivars.